2019
DOI: 10.18826/useeabd.510426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Balance Properties of Hypermobility in Boys

Abstract: Bu çalışma erkek çocukların hipermobilite oranını belirlemek ve dinamik dengeleri arasındaki farkı karşılaştırmak amacıyla yapılmıştır. Materyal ve Yöntem: Şanlıurfa ilinde yaşayan 156 sedanter erkek çocuk (yaş ortalamaları: 11,7±0,672 yıl) Helsinki kriterleri'ne göre hazırlanmış bilgilendirilmiş olur alma formları ile gönüllük esasına dayalı, velilerinden izin alınarak çalışmaya katılmıştır. Hipermobilite ölçümleri Beighton kriterlerine göre değerlendirilmiş, kesim noktası 4 olarak alınarak 4 ve üzeri puan al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Data were calculated separately for both arms and legs. Upper extremity applications were determined by the formula [26]:…”
Section: Data Collection Body Composition Measurementsmentioning
confidence: 99%
“…Data were calculated separately for both arms and legs. Upper extremity applications were determined by the formula [26]:…”
Section: Data Collection Body Composition Measurementsmentioning
confidence: 99%
“… 23 , 24 In this regard, they suggested that a lower ability of resilience could contribute to failure experiences, avoidance of activities of daily living, and difficulties in daily life. 16 , 25 Resilience has become one of the key concepts in understanding the possibility of subjective wellness in SCZ. Previous studies have shown the associations of resilience in SCZ with self-esteem and hopelessness, 26 but lack of knowledge about stigma and negative automatic thoughts about MetS of SCZ, as well as deficiency of these information appear to be shortcomings to the active monitoring of physical health in patients with SCZ.…”
Section: Introductionmentioning
confidence: 99%